Talking new politics - Sen, Jai, 1946-; Saini, Mayuri; World Social Forum (New Delhi : Zubaan, 2005)
Contributed articles published in ancillary meetings as run up to World Social Forum 2004 on social change and prediction.
Subtitle on cover: Are other worlds possible?
"Open space seminar series"--P. 196.
Keywords: Social change; Social prediction